THE IMPACT OF OVERCONFIDENCE AND OPTIMISM ON INVESTMENT DECISION ON INDIVIDUAL INVESTOR IN INDONESIA - Reni Rezki Pratiwi; Farah Margaretha Leon (Universitas Kristen Krida Wacana, 2019)
This study aims to analyze the impact of Overconfidence and Optimism on Investment Decisions on Individual Investors in Indonesia. The data used in this study was obtained by spreading 200 questionnaires on individual investors, but a decent processed as many as 151 questionnaires using a likert scale. The research design used is hypothesis testing, while the analysis tool used is SPSS by using multiple regression method and correlation method. The results of this study indicate that there is no influence overconfidence on investment decisions and second hypothesis of this study there is a positive influence of optimism on investment decisions. The implication of this study is that investment managers should be able to offer high return portfolio despite high risk because there is optimism factor at the moment of decision making and for investor although having high level of optimism it is necessary to consider the risk in each investment decision.Keywords: investment decision, overconfidence, optimism